Pengaruh Etos Kerja Dan Kompetensi Kewirausahaan Terhadap Kinerja UMKM Pada Anggota Asosiasi UMKM Muaro Jambi (ASUMKMUJA) - Evi Nur Azizah; Mohammad Orinaldi; Rohana Rohana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to determine the influence of work ethic and entrepreneurial competency on MSME performance among members of the Muaro Jambi MSME Association (ASUMKMUJA). This research uses quantitative research methods and uses primary data. Samples were taken using a purposive sampling method and a sample of 56 MSME actors was obtained from 124 members of the Muaro Jambi MSME association using the Slovin formula. Based on the results of research using the t test, it shows that Work Ethic has a significantly positive effect on MSME performance among members of the Muaro Jambi MSME Association (ASUMKMUJA). And Entrepreneurial Competence also has a significant positive effect on MSME Performance among members of the Muaro Jambi MSME Association (ASUMKMUJA). Then the results obtained using the f test show that Work Ethic and Entrepreneurial Competence on MSME Performance among Members of the Muaro Jambi MSME Association (ASUMKMUJA) have a significant simultaneous effect on MSME performance as shown by an R square value of 62.9%.